AMMONITE BIOZONATION AND LITHO-/CHRONOSTRATIGRAPHY OF THE CRETACEOUS IN SAKHALIN AND ADJACENT TERRITORIES OF FAR EAST RUSSIA - Yazykova E. (My University, 2004)
The stratigraphy and ammonite faunas of the Cretaceous succession in Sakhalin are discussed. A high-resolution bio-stratigraphic zonation (24 zones in total) is proposed; it is correlated with adjacent areas and corresponds well to inoce-ramid and radiolarian zones. The definition of all stage and some substage boundaries in Sakhalin is discussed, and possi-bilities for interregional and global correlations are assessed. In addition, the main mass extinction and faunal turnover events recognised in these sections are taken into consideration.
Keywords: Cretaceous; Ammonites; Stratigraphy; Bioevents; Palaeoecology; Sakhalin; Far East Russia; Mesozoic::Cretaceous; Мезозой::Меловая